Hegemoni Kekuasaan Penguasa terhadap Pendidikan Bermoral dalam Tataran Ontologis, Epistimologis dan Aksiologis - Gilang Sukma Permana; Irawan Irawan; Tedi Priatna (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The world of education and teaching in this contemporary phase cannot be separated from hegemonic relations between policy stakeholders. Policymakers who will exist in 2022-2023 are involved with Gen X, individuals born in the 1965-1980 period. In its power as a policy maker, education is directed and expected to become a concrete step like a machine that produces moral human beings. Morals in education are intended so that students can have the values of love, love each other within the limits of norms and have commendable ethics both in religious and cultural values. The problem in this research concerns contemporary issues regarding the hegemony of power over the moral educational process in the view of the philosophy of science at the ontological, epistemological and axiological levels. The aim of this research is to reveal the hegemony of power over the moral educational process in the view of the philosophy of science at the ontological, epistemological and axiological levels. The method used in this research is qualitative with a philosophy of science approach. From the perspective of the philosophy of science, the hegemony of power over moral education goes through three phases; ontological as a search for the nature of what and why of moral education; epistemological as a review of the hegemony of power towards moral education in the philosophical aspect and axiological as a review of the usefulness of aspects of the hegemony of power towards moral education. The results of the research show that there is a hegemony of rulers who have power which is marked by the symbol of the Minister of Religion as the ruler of Gen With this moral education, educators will continue to be wise and wise in their lives, because the function of Islamic education in Indonesia is to improve and teach morals to their students so that they become human beings who have moral values.